Sentenced! Writing it Differently: "Life" and Death Row in Catherine Mavrikakis's Les Derniers jours de Smokey Nelson. (June 2015) - Killick, Rachel
Abstract : With a title closely recalling Victor Hugo's Le Dernier jour d'un condamné (1829) and its nineteenth-century attack on the death penalty, Les Derniers jours de Smokey Nelson (2011) might appear at a cursory glance as merely a twenty-first-century replay of a debate that still rumbles on in western societies as a suppressed element in the popular mindset, even fifty years after the widespread abolition of capital punishment. This reflection is certainly carried forward as one aspect of Catherine Mavrikakis's 2011 novel. More fundamentally, however, she presents the life and death of Smokey Nelson as tied to – and indeed symbolic of – the life imprisonment/death-row existence that we all, as human beings, inevitably inhabit. Locked each in his or her own 'cell', the four protagonists of the novel offer, turn by turn, their individual versions of their incarceration, an incarceration transcended for the reader by Mavrikakis's virtuoso orchestration of the multiple voices of their predicament. Articulating difference, exposing similarity, she gradually and inventively establishes, sentence by telling sentence, an artistic control that challenges the arbitrary sentencing of personality, circumstance and mortality and that points instead to the death-defying potential of creative self-affirmation.